2006
DOI: 10.1200/jco.2006.24.18_suppl.7008
|View full text |Cite
|
Sign up to set email alerts
|

Lung Adjuvant Cisplatin Evaluation (LACE): A pooled analysis of five randomized clinical trials including 4,584 patients

Abstract: 7008 Background: Several recent trials have shown a benefit of adjuvant cisplatin-based chemotherapy on overall survival (OS) in patients with non-small cell lung cancer (NSCLC). The aim of the Lung Adjuvant Cisplatin Evaluation (LACE) is to identify treatment options associated with a higher benefit, or groups of patients benefiting more from adjuvant chemotherapy. Methods: Individual patient data were collected and pooled from the five largest trials (ALPI, ANITA, BLT, IALT and JBR10) of cisplatin-based che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
81
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(90 citation statements)
references
References 0 publications
1
81
0
4
Order By: Relevance
“…Patients with stage IV lung adenocarcinoma whose tumors harbor EGFR mutations in exon 19 or 21 are reported to have response rates >70% and prolonged progression‒free survival after treatment with the EGFR tyrosine kinase inhibitors (TKIs) gefitinib or erlotinib (graded according to the American Joint Committee on Cancer staging system) 18‐22. The presence of EGFR mutations is reported to predict response to EGFR TKI therapy better than smoking status and may be a positive prognostic factor in patients with advanced lung adenocarcinoma irrespective of therapy 18, 23…”
mentioning
confidence: 99%
“…Patients with stage IV lung adenocarcinoma whose tumors harbor EGFR mutations in exon 19 or 21 are reported to have response rates >70% and prolonged progression‒free survival after treatment with the EGFR tyrosine kinase inhibitors (TKIs) gefitinib or erlotinib (graded according to the American Joint Committee on Cancer staging system) 18‐22. The presence of EGFR mutations is reported to predict response to EGFR TKI therapy better than smoking status and may be a positive prognostic factor in patients with advanced lung adenocarcinoma irrespective of therapy 18, 23…”
mentioning
confidence: 99%
“…8 A meta-analysis of recent adjuvant, cisplatin-based chemotherapy trials also did not report any survival benefit from the use of chemotherapy for patients with stage I NSCLC. 9 The Cancer and Leukemia Group B (CALGB) 9633 study reported a 12% reduction in mortality at 4 years with adjuvant carboplatin plus paclitaxel in patients with stage IB NSCLC; however, after a longer follow-up, the improvement in survival no longer was significant. 10 Subgroup analysis showed that patients with stage IB NSCLC who had tumors that measured 4 cm did derive a survival benefit from the use of adjuvant chemotherapy.…”
mentioning
confidence: 99%
“…In an attempt to understand the overall results of the large adjuvant trials that have occurred since the 1995 metaanalysis, an individual patient meta-analysis of the five largest, cisplatin-based studies was conducted (ALPI, BLT, IALT, JBR.10, and ANITA)-the Lung Adjuvant Cisplatin Evaluation (LACE). That study found a 5.3% absolute survival advantage at 5 years (HR, 0.89; 95% CI, 0.82-0.96; p ϭ .004) for adjuvant cisplatin therapy overall [10], thus reinforcing the need to adequately power adjuvant trials for this range of benefit. The stage IB subset analysis trended toward benefit (HR, 0.92), but failed to reach statistical significance (95% CI, 0.78 -1.10), while a detriment for chemotherapy was suggested in stage IA patients (HR, 1.41; 95% CI, 0.96 -2.09).…”
Section: Adjuvant Chemotherapy 2003-2006mentioning
confidence: 91%